Exploring the impact of multidecadal environmental changes on the population genetic structure of a marine primary producer. Issue 9 (30th March 2017) - Lundholm, Nina; Ribeiro, Sofia; Godhe, Anna; Rostgaard Nielsen, Lene; Ellegaard, Marianne
Abstract: Many marine protists form resting stages that can remain viable in coastal sediments for several decades. Their long‐term survival offers the possibility to explore the impact of changes in environmental conditions on population dynamics over multidecadal time scales. Resting stages of the phototrophic dinoflagellate Pentapharsodinium dalei were isolated and germinated from five layers in dated sediment cores from Koljö fjord, Sweden, spanning ca. 1910–2006. This fjord has, during the last century, experienced environmental fluctuations linked to hydrographic variability mainly driven by the North Atlantic Oscillation. Population genetic analyses based on six microsatellite markers revealed high genetic diversity and suggested that samples belonged to two clusters of subpopulations that have persisted for nearly a century. We observed subpopulation shifts coinciding with changes in hydrographic conditions. The large degree of genetic diversity and the potential for both fluctuation and recovery over longer time scales documented here, may help to explain the long‐term success of aquatic protists that form resting stages. Abstract : The manuscript illustrates the use of revived resting stages of aquatic protists for exploring responses of an organism to environmental changes over temporal scales, here almost 100 years. We found an overall stability of the population coupled with subpopulations shifting, depending on the environmental conditions, supporting that rapid evolutionary shifts happen in aquatic protists. Live resting stages may serve as time capsules from the past and can be used to explore previous and predict future environmental changes.